(untitled) (TEST Trento Student Law Review, 2025)
This article examines the interplay between copyright law and emerging digital technologies, focusing on several key components: the constitutional basis of copyright law, the doctrine of fair use, secondary liability, the DMCA safe harbor provisions, and automated copyright enforcement technologies, particularly YouTube’s ContentID system. In Part I, the paper outlines these foundational elements. Part II builds upon this framework to analyze recent developments in online copyright enforcement, highlighting existing challenges and proposing potential solutions to improve the effectiveness and fairness of these enforcement mechanisms.